(untitled) (Entrepalavras, 2025)
This article investigates two constructions in American English used to express service provision: the Service Provision Causative Construction (SPCC), as in "I had my nails done," and the Service Provision Transitive Construction (SPTC), as in "I did my nails." To the extent that these constructions seemingly challenge the Principle of Non-Synonymy (Goldberg, 1995), they present an issue for functionalist framework Principle. Through the lens of Usage-Based Construction Grammar (UBCG), this paper argues that while both constructions evoke a service provision event, the SPTC also evokes an additional event and profiles different elements of the scene, suggesting a greater degree of involvement by the subject referent. This difference in profiling and involvement helps explain why speakers might choose one construction over the other, thus providing evidence in favor the Non-Synonymy Principle and contributing to a deeper understanding of the relationship between form and meaning in service provision expressions.